Zakat Compliance and Economic Well-Being in Indonesia - Ghozali, Achmad (Yayasan Sinergi Kawula Muda, 2024)
This study explores the complex relationship between zakat compliance, personal income, education level, religious knowledge, understanding of zakat, and financial well-being in Indonesia. Using numerical methods, information from a group of 120 people was examined using Confirmatory Factor Analysis (CFA) and Structural Equation Modelling - Partial Least Squares (SEM-PLS). Descriptive statistics provided a summary of the sample, and CFA verified the dependability and accuracy of the measurement model. The SEM-PLS study shows an important relationship between zakat compliance and economic well-being, with individual income, education level, religious awareness, and zakat literacy influencing this interaction. The results of this study help us understand how social and economic elements, along with religious beliefs, come together to influence economic outcomes in an Islamic setting. The real implication of this research could be the basis for stakeholders who have the authority to increase the level of zakat literacy.